2019
DOI: 10.1021/acs.jmedchem.9b00683
|View full text |Cite
|
Sign up to set email alerts
|

Can Cysteine Protease Cross-Class Inhibitors Achieve Selectivity?

Abstract: Cysteine proteases are important targets for the discovery of novel therapeutics for many human diseases. From parasitic diseases to cancer, cysteine proteases follow a common mechanism, the formation of an encounter complex with subsequent nucleophilic reactivity of the catalytic cysteine thiol group toward the carbonyl carbon of a peptide bond or an electrophilic group of an inhibitor. Modulation of target enzymes occurs preferably by covalent modification, which imposes challenges in balancing cross-reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 234 publications
0
67
0
4
Order By: Relevance
“…A variety of studies have been conducted on optimization strategies for the interactions of different classes of inhibitors with the S1, S2 and S3 binding sites of cruzain and related cysteine proteases [13,14,19,20]. Nonetheless, far less is known about the attainable interactions at S1′ for dipeptidyl nitrile inhibitors [21].…”
Section: Resultsmentioning
confidence: 99%
“…A variety of studies have been conducted on optimization strategies for the interactions of different classes of inhibitors with the S1, S2 and S3 binding sites of cruzain and related cysteine proteases [13,14,19,20]. Nonetheless, far less is known about the attainable interactions at S1′ for dipeptidyl nitrile inhibitors [21].…”
Section: Resultsmentioning
confidence: 99%
“…Despite its ability to rescue mice of a lethal experimental T. cruzi infection and reduce parasite growth in dogs, preclinical safety and toxicology studies revealed substantial side effects of K777 in primates and dogs, even when administered in low doses [10,11]. Current research is being focused on reversible Cz inhibitors, as these are assumed to overcome possible off-target effects [12]. Drug repurposing programs of different pharmaceutical companies have recently put forward reversible inhibitors of Cz as potential drug candidates [13].…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme has a high degree of structural identity with the human enzymes cathepsin K, cathepsin L, cathepsin S and high sequence homology with cathepsin B that are involved in many physiological processes (KRAMER; TURK; TURK, 2017). Therefore, the knowledge generated from Cz inhibition can be transposed to its mammalian counterparts and vice-versa (CIANNI et al, 2019). The same concept can be applied to another protozoan parasite CPs recently used as a pharmacological target based on in vitro and in vivo models, as the cysteine protease B of the Leishmania mexicana (LmCPB), the obligate intracellular protozoan parasite that causes the cutaneous form of leishmaniasis (CROFT;COOMBS, 2003;SIQUEIRA-NETO et al, 2018).…”
Section: Materials Andmentioning
confidence: 99%
“…A variety of studies have been conducted on optimization strategies for the interactions of different classes of inhibitors with the S1, S2 and S3 binding sites of cruzain and related cysteine proteases. (see chapter I) CIANNI et al, 2019;SCHMITZ et al, 2019). Nonetheless, far less is known about the possible interactions at S1′ for dipeptidyl nitrile inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation